Compliance on Diet and Exercise among Diabetic Patient in Referral Hospital of Morang District - Rijal, Shashi Sharma; Paudel, Diksha; Bhandari, Bhawana; KC, Takma; Mainali, Uttar; Chapagain, Pratiksha; Basnet, Sandhya (Journal of Advanced Academic Research, 2022)
Diabetes is a serious health problem that threatens the quality of life of with diabetes, the success of long term maintenance therapy for diabetes depends largely on the patient compliance with diet and exercise. Thus, this study aim to assess the compliance on Diet and Exercise among diabetic patient in a Referral Hospital of Morang District.Methodology: A cross sectional descriptive study was conducted among type 2 diabetic patient in medical OPD of Koshi Hospital   through face to face interview Data were organized, verified and analyzed using the Statistical Package for Social Sciences, version 17.Results: A total of 141 participants were included in this study, of them 55.3% were males. The rate of compliance to diet and exercise was 48.2% and 22.7%, respectively. Compliance to diet was higher in people of age above 50 years (p=0.029) and those who are single (p=0.037), patient with duration of diagnosis less than 5 years (p=0.01) and those who had dietary counselling (p=0.007).  The rate of compliance to exercise among type-2 diabetes patients in Morang district was low, and it could be attributed to a combination of several socio-demographic and clinical factors.